Effectiveness of Cancer Patient Navigator Program to Reduce Caregiver Burden: A Systematic Review - Marisco Rikumahu; Allenidekania Allenidekania; Hening Pujasari; Dewi Gayatri (Jurnal Kesehatan Vokasional, 2025)
Background: Cancer is a major disease that significantly affects global public health. In Indonesia, the number of cancer patients continues to increase, requiring innovative approaches in the cancer care system.Objective: This study aims to evaluate the effectiveness of cancer patient navigator programs in reducing caregiver burden, particularly among cancer patients.Methods: This systematic review followed the PRISMA guidelines and used inclusion criteria that included full-text articles published in English and quantitative studies. Literature searches were conducted in various academic databases using relevant keywords.Results: Out of 3,583 records retrieved, 6 studies met the criteria for further analysis. The results also showed that patient navigator programs can significantly reduce caregiver burden through improved education, emotional support, and access to healthcare services.Conclusion: The implementation of cancer patient navigator programs in Indonesia has the potential to reduce caregiver burden and improve the quality of cancer patient care. Recommendations for further research and health policy are also included.